A Multi-OMICs Approach Sheds Light on the Higher Yield Phenotype and Enhanced Abiotic Stress Tolerance in Tobacco Lines Expressing the Carrot lycopene β-cyclase1 Gene - Moreno, Juan C.; Martinez-Jaime, Silvia; Kosmacz, Monika; Sokolowska, Ewelina M.; Schulz, Philipp; Fischer, Axel; Luzarowska, Urszula; Havaux, Michel; Skirycz, Aleksandra (Frontiers in Plant Science, 2021)
Recently, we published a set of tobacco lines expressing the Daucus carota (carrot) DcLCYB1 gene with accelerated development, increased carotenoid content, photosynthetic efficiency, and yield. Because of this development, DcLCYB1 expression might be of general interest in crop species as a strategy to accelerate development and increase biomass production under field conditions. However, to follow this path, a better understanding of the molecular basis of this phenotype is essential. Here, we combine OMICs (RNAseq, proteomics, and metabolomics) approaches to advance our understanding of the broader effect of LCYB expression on the tobacco genome and metabolism. Upon DcLCYB1 expression, the tobacco genome (~2000 genes), proteome (~700 proteins), and metabolome (26 metabolites) showed a high number of changes in the genes involved in metabolic processes related to cell wall, lipids, glycolysis, and secondary metabolism. Gene and protein networks revealed clusters of interacting genes and proteins mainly involved in ribosome and RNA metabolism and translation. In addition, abiotic stress-related genes and proteins were mainly upregulated in the transgenic lines. This was well in line with an enhanced stress (high light, salt, and H2O2) tolerance response in all the transgenic lines compared with the wild type. Altogether, our results show an extended and coordinated response beyond the chloroplast (nucleus and cytosol) at the genome, proteome, and metabolome levels, supporting enhanced plant growth under normal and stress conditions. This final evidence completes the set of benefits conferred by the expression of the DcLCYB1 gene, making it a very promising bioengineering tool to generate super crops.